Effect of side group on mechanically induced conductance switching in 4,4′-dipyridyl-based single-molecule junctions - Wan, Zhen; Zheng, Chang-Feng; Liu, Lin; Ge, Yun-Long; Zhang, Guang-Ping; Qiu, Shuai; Wang, Hui; Li, Zong-Liang (Chinese physics B, 2025)
The forming processes of 4,4′-dipyridyl-based single-molecule junctions and mechanically induced conductance switching as well as the side-group effects are systematically investigated by applying the ab initio -based adiabatic geometric optimization method and the one-dimensional transmission combined with three-dimensional correction approximation (OTCTCA) method. The numerical results show that for the 4,4′-dipyridyl with a π -conjugated phenyl-phosphoryl or diphenylsilyl side group, the pyridyl vertically anchors on the second atomic layer of the pyramid-shaped Au tip electrode at small inter-electrode distances by laterally pushing the apical Au atom aside, which induces stronger pyridyl-electrode coupling and high-conductance state of the formed junctions. As the inter-electrode distance increases, the pyridyl shifts to the apical Au atom of the tip electrode. This apical Au atom introduces additional scatterings to the tunneling electrons and significantly decreases the conductance of the junctions. Furthermore, for the 4,4′-dipyridyl with a phenyl-phosphoryl side group, the probability of manifesting the high-conductance state is decreased due to the oxygen atom reducing the probability of the pyridyl adsorbing on the second layer of Au tip electrode. In contrast, for the 4,4′-dipyridyl with a non-conjugated cyclohexyl-phosphoryl side group, the steric hindrance from the bulky cyclohexyl group leads the molecule to preferentially form the O–Au contact, which prevents both the high conductance and mechanically induced conductance switching of the junction. Our results provide a theoretical understanding of the side-group effects on electronic transport properties of single-molecule junctions, offering an alternative explanation for the experimental observations.